CULTURAL TRANSITIONS AND EDUCATIONAL PATHWAYS: INDONESIAN STUDENTS’ EXPERIENCES IN DEVELOPING NUMERACY AND ADAPTATION ABROAD - Safitri Yosita Ratri; Fery Muhamad Firdaus; Yeni Rakhmawati; Nina Maadad; Igusti Darmawan (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study explores the adaptation and learning experiences of Indonesian elementary school students who are pursuing education in Australia. Using a qualitative case study approach, data were collected through interviews with students, parents, and teachers, and analyzed using thematic coding (open, axial, and selective coding). Four participants were purposively selected to represent variations in gender and grade levels, coded as A1 (male, upper grade), A2 (male, lower grade), B1 (female, upper grade), and B2 (female, lower grade). The analysis revealed five central themes: adaptation, learning methods, mathematics development, parental involvement, and reward/behavioral strategies. Findings indicate that younger students benefitted from concrete and game-based learning approaches, while older students adapted more proactively through application-oriented and independent strategies. Across all cases, parental involvement and positive reinforcement were identified as critical factors in supporting student adjustment and motivation. These results highlight the dual strengths of Indonesian students in maintaining structured learning habits from their home culture while successfully adapting to new educational expectations abroad. The study suggests that culturally responsive pedagogy, combined with strong home–school collaboration, can enhance both academic and social outcomes for Indonesian students in international schooling contexts.